SOCIAL COMPETENCE FORMATION AMONG TEENAGERS FROM HUMANIST TREND MULTIPLE-AGED GROUPS - Larisa A. Krapivina (Obrazovanie i Nauka)
The paper studies the problems of social development of adolescents in multiple-aged groups (MAG).Methods. The methods involve socio-personal approach, consideration of the subject in a certain ideological humanistic orientation, comparative analysis, and comparison of historical facts, the study of social phenomena of different ages, long-term scientific observations, reflections, a retrospective analysis of personal experience.Results. The author describes objective conditions for the uprise of extremist, subcultural youth of multiple-aged groups, and the reasons whence they begin to perform distinctive functions that are specific for teenagers. Options for models of MAG humanistic educational systems formed in Russian and foreign social and pedagogical practice are listed. A complex of pedagogical conditions provided for the formation of social competence of adolescents in multiple-aged associations of humanistic orientation is considered. It has been found that this type of system is characterized by the following features: the principle of voluntary association of people, independence of subjects, rapid adaptation to changing socio-cultural situation, a variety of activities by interests, alternating change of activities, conflict resolution within the team, a high level of team spirit, selfmanagement, the creative nature of educational process, upbringing, socialization and self-realization. A brief description of conditions for development of fundamental human values among adolescents and formation of new specific complicated humanistic human and personal relations in global world is given.Scientific novelty. The author studies the following concepts: educational system of multiple-aged associations, teenager social competence, ambivalent behavior, emotional and moral compass of personality, invisible assets of the team, emergent effect of multiple-aged groups, inter-age communication. It was found that the specificity of MAG educational potential is determined by the conditions for the appearance of multiple-aged associations as a system-forming principle; all members of association are freely operating subjects, which consciously accept external restrictions caused by multiple-aged membership of participants of any activity. Relations of freedom, an openness, trust, equality, safety, collective unity in MAG provide introduction of emerging effect of display of the hidden assets of a personality. The substantial part of MAG space allows to create for its each member enough of educational reality situations and representations about actions in them that creates conditions for positive changes both the separate person, and all community as a whole.The humanistic orientation of MAG activity is that it’s each participant, joining cultural traditions, ethnic, civil and universal values, adopting life experience of others, keeps own uniqueness.Practical significance. Based on the Children and Youth Public Centre «Carabela» that has been working in Yekaterinburg for more than fifty years, the author discloses how to use the technology of inter-age communication and interaction to provide the continuity of traditions, to preserve historical memory, to transfer humanistic ideas in the chain of generations, and to create personality with sound emotional and moral compass. It is shown that, on the one hand, subjective component complicates the educational system, but on the other – simplifies basic processes, functions, qualities, factors and connections of the whole educational system; provides the link between «educational and practical life»; allows teachers to align the ambivalent process of formation of social competence among adolescents.